Exacerbated symptoms in Blastocystis sp.-infected patients treated with metronidazole: two case studies - Rajamanikam, Arutchelvan; Kumar, Suresh; Samudi, Chandramathi; Kudva, Madhav (Springer Verlag (Germany), 2018)
Blastocystis sp. is a gastrointestinal (GI) protozoan parasite reported to cause non-specific GI symptoms including diarrhea, flatulence, abdominal pain, and nausea. Complete eradication of Blastocystis sp. is rather challenging even with the drug of choice, i.e., metronidazole. Here, we report on two Blastocystis sp.-infected individuals, who presented increased parasite load and exacerbated symptoms upon treatment with the usual recommended dosage and regime of metronidazole. The two studies uniquely demonstrate for the first time a cyst count as high as fivefold more than the original cyst count before treatment and show an exacerbation of GI symptoms despite treatment. The study provides additional support in recognizing metronidazole resistance in Blastocystis sp. and its consequences towards the pathogenicity of the parasite.